Hydrography in the trajectory of Riobaldo in “Grande Sertão: Veredas” - Carneiro, Marina de Fátima Brandão (2014)
In the narrative of Grande Sertão: veredas realizes the great importance of hydrography revealing the paths traversed by Riobaldo, the zigzag by hinterlands of General, since he was a kid and, especially, with the gangs of roughnecks and his great love, Diadorim. In this fictional space are three watersheds of Minas Gerais: the São Francisco River, that part your life in half; the Rio Pardo and the Jequitinhonha River where several episodes of his life unfold. In this context, this work has as objective to analyze the importance and role of hydrography as support for the fictional space work Grande Sertão: veredas by João Guimarães Rosa, giving meaning to complex and contentious trajectory of its main character, Riobaldo. The methodological approach has opted analytic-synthetic study with readings and analysis of the work already cited and other authors who analyzed and wrote on the subject.